2014
DOI: 10.1080/19443994.2014.910841
|View full text |Cite
|
Sign up to set email alerts
|

Current status and future directions of MED-TVC desalination technology

Abstract: Desalination has now become one of the major water treatment processes in several countries around the world where shortage of water is a serious problem. Energy consumption is a vital economic factor in selecting the type of desalination processes because current desalination processes require large amount of energy which is costly. Multi-effect desalination system with thermal vapor compression (MED-TVC) is particularly more attractive than other thermal desalination systems due to its low energy consumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Currently, the capacity of commercial MED-TVC plants ranges from 70,000 to 80,000 ton/d and the capacity of commercial MED-MVC plants is below 10,000 ton/d [88,89]. Integrating TVC with MED can also lead to reduced thermal energy consumption by utilizing part of the vapor coming from the last effect [90].…”
Section: Multi-effect Distillationmentioning
confidence: 99%
“…Currently, the capacity of commercial MED-TVC plants ranges from 70,000 to 80,000 ton/d and the capacity of commercial MED-MVC plants is below 10,000 ton/d [88,89]. Integrating TVC with MED can also lead to reduced thermal energy consumption by utilizing part of the vapor coming from the last effect [90].…”
Section: Multi-effect Distillationmentioning
confidence: 99%
“…MED‐TVC has been commercially installed and one of them is Yanbu Phase 2 expansion in Saudi Arabia with capacity ≈150 000 m 3 day −1 . [ 55 ] Many attempts have been made to improve the operation of MED‐TVC system through experimental and mathematical approaches. The exergy and exergoeconomic analysis carried out by Elsayed et al identified the component that experienced the highest entropy generation in the MED‐TVC.…”
Section: Desalination System Hybridizationmentioning
confidence: 99%
“…In Marafiq plant, the integration of MED‐TVC with a gas‐steam combined power cycle produces 2750 MW of power and 800 000 m 3 day −1 of water. [ 55 ] The case study conducted by Ihm et al based on Yanbu Phase 3 and Ras Al‐Khair Phase1 power and desalination cogeneration plants in the Middle East indicated that, the fuel energy of thermal‐based desalination was greatly benefited from the high efficiency of combined cycle power plant due to a lowered steam value. [ 56 ] Utilization of oil refinery plants waste gases to power a MSF process has been demonstrated.…”
Section: Strategies For Energy Reduction In Desalination Processesmentioning
confidence: 99%
“…Table 4 shows the MED plants that have been used for validation purposes. Some main specifications are also provided for these plants [8,14,[33][34][35]. Focus is given on having a sample with large enough differences so that the conclusions are as solid as possible.…”
Section: Validation Of the Proposed Cost Correlationmentioning
confidence: 99%